THE QUALIMETRY IN THE MANAGEMENT OF MARKETING COMMUNICATIONS OF THE INSTITUTION OF GENERAL SECONDARY EDUCATION (Comparative Professional Pedagogy, 2023)
The article describes the system of qualitative factor-criterion submodels in the management of marketing communications of a general secondary education institution. The specified factor-criterion submodels are considered from the standpoint of the tools of modern educational marketing science.In modern pedagogical theory and practice, measuring and evaluating the quality of the educational process becomes one of the key problems that has received the status of an independent scientific direction - pedagogical qualimetry. The development of the education quality assessment system is aimed at the implementation of qualitative monitoring of education and the qualitative measurement of its main components: curricula and training programs of disciplines, educational content, educational technologies, pedagogical personnel, and finally - educational results. The relevance of the problem of education quality measurement is determined by a number of objective factors, among which the following should be highlighted: the global and intensive introduction of modern information technologies into the educational process, the focus of professional education on a new learning outcome. The article can be useful for heads of institutions of general secondary education, relevant employees of governing bodies in the field of education, institutions of the postgraduate pedagogical education system. We consider the mastering at least one of the qualitative methods will help arm managers with a unique and effective tool for evaluating the results achieved and successfully solve both partial tasks of a measurement nature and the strategic task of improving the quality of education in general.
Keywords: management; qualimetry; institution of general secondary education; factor-criterion submodel; system; marketing; marketing communications